2013
DOI: 10.1038/onc.2012.582
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming governs EcSOD expression during human mammary epithelial cell differentiation, tumorigenesis and metastasis

Abstract: Expression of the antioxidant enzyme EcSOD in normal human mammary epithelial cells was not recognized until recently. Although expression of EcSOD was not detectable in non-malignant human mammary epithelial cells (HMEC) cultured in conventional two-dimensional (2D) culture conditions, EcSOD protein expression was observed in normal human breast tissues, suggesting that the 2D-cultured condition induces a repressive status of EcSOD gene expression in HMEC. With the use of laminin-enriched extracellular matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 40 publications
(51 reference statements)
4
71
0
Order By: Relevance
“…The increased ROS may promote mutagenesis and may also render tumor cells more prone to expand and produce distant metastases (34)(35)(36)(37). In agreement, overexpression of the antioxidant SOD3 inhibits murine breast cancer cell metastasis (38), and the ROS scavenger N-acetyl-cysteine reduces the tumorigenicity of murine melanoma cells (15). High endogenous ROS concentrations in malignant cells may also render these cells more vulnerable to further stresses (34,39,40).…”
Section: Gr1mentioning
confidence: 58%
“…The increased ROS may promote mutagenesis and may also render tumor cells more prone to expand and produce distant metastases (34)(35)(36)(37). In agreement, overexpression of the antioxidant SOD3 inhibits murine breast cancer cell metastasis (38), and the ROS scavenger N-acetyl-cysteine reduces the tumorigenicity of murine melanoma cells (15). High endogenous ROS concentrations in malignant cells may also render these cells more vulnerable to further stresses (34,39,40).…”
Section: Gr1mentioning
confidence: 58%
“…Antioxidants like NAC and vitamin C could prevent HIF stabilization and diminish MYC-mediated tumorigenesis38. Other studies also reported antitumorigenic results of antioxidant treatments, including overexpression of SOD3, which inhibited breast cancer metastasis indicating the potential anti-tumorigenic effect of restoring extracellular superoxide scavenging capacity [73][74][75]. However, most clinical trials were failed to show beneficial effects of antioxidants on a variety of cancer [76,77].…”
Section: Regulating Ros Levels To Treat Cancer Decrease Ros Levelsmentioning
confidence: 99%
“…Emerging evidence from lrECM 3D culture suggests epigenetic regulation of gene expression by the ECM signaling in cancer cells (Lelievre, 2010; Li et al ., 2016; Teoh‐Fitzgerald et al ., 2014). However, ECM‐regulated expression and functions of lncRNA have not been examined in Claudin‐low breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%